2001
DOI: 10.1159/000047156
|View full text |Cite
|
Sign up to set email alerts
|

Reparation of a Severe Case of Aplasia cutis congenita with Engineered Skin

Abstract: Aplasia cutis congenita (ACC) is an uncommon congenital malformation. It is characterized by defects of the skin that occur most frequently on the scalp along the midline, but can also be localized on the trunk, face and limbs, usually with a symmetrical distribution. When it is localized in the skull it can extend to the dura mater, leaving only the thin pia mater to protect the brain. The most common complications related to this disorder are infection, hemorrhage, and, in defects localized on the vertex, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Substitutes for split-thickness skin grafts have been used in dealing with the scalp defects but are most useful for secondary deformities resulting from scalp rotations, including: BiobraneĀ®, cultured epithelial autographs, Dermal Regeneration Template [53,54], composite graft of cultured autologous fibroblasts and keratinocytes [55], acellular dermal graft with cultured epithelial autografts [56,57], recombinant human fibroblast graft (TraferminĀ®) [28], petrolatum dressings [28], and silicone elastomer membrane [39]. In both our patients, the donor sites resulting from the rotation of the scalp flaps and the original abdominal skin defects were managed temporarily with BiobraneĀ® and later definitively covered with cultured epithelial cell autografts harvested from the groin.…”
Section: Management Of Scalp Defectsmentioning
confidence: 99%
“…Substitutes for split-thickness skin grafts have been used in dealing with the scalp defects but are most useful for secondary deformities resulting from scalp rotations, including: BiobraneĀ®, cultured epithelial autographs, Dermal Regeneration Template [53,54], composite graft of cultured autologous fibroblasts and keratinocytes [55], acellular dermal graft with cultured epithelial autografts [56,57], recombinant human fibroblast graft (TraferminĀ®) [28], petrolatum dressings [28], and silicone elastomer membrane [39]. In both our patients, the donor sites resulting from the rotation of the scalp flaps and the original abdominal skin defects were managed temporarily with BiobraneĀ® and later definitively covered with cultured epithelial cell autografts harvested from the groin.…”
Section: Management Of Scalp Defectsmentioning
confidence: 99%
“…It is already possible to gain access to fetal cells and to grow them selectively. This offers therapeutic potential (208), and such tissue engineering has already occurred (209).…”
Section: What Does the Future Hold?mentioning
confidence: 99%
“…13Y15 Other genetic anomalies associated with ACC include chromosomal aberrations, trisomy 13, deletion syndromes (4p), and genetic mutations. 5,6,16 Aplasia cutis congenita also has been associated with a number of specific syndromes. Suarez et al 5 reported on 3 of 36 patients with ACC who had Adams-Oliver syndrome and 1 patient who had cutis marmorata telangiectasia syndrome.…”
mentioning
confidence: 99%
“…Setleis, AndersonHollister-Szalay, and Johanson-Blizzard and Goltz are syndromes also associated with ACC. 5,16,17 Teratogens have been posed as another hypothesis for the etiology of ACC. Fetal exposure to certain teratogens during pregnancy has been blamed for causing ACC.…”
mentioning
confidence: 99%
See 1 more Smart Citation